ANALISIS PENGARUH PENGUNGKAPAN INFORMASI KEUANGAN BASIS INTERNET TERHADAP BIAYA MODAL EKUITAS DENGAN PENDEKATAN PRICE EARNING GROWTH RATIO PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS KOMPAS 100 - Rossy Amalina Anjani; Emrinaldi Nur DP; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study examines the influence of internet financial reporting that consists of 4 indicators, content, reporting frequency, technology, and user support to cost of equity capital with price earning growth ratio approach. Sampels in this study are 100 companies that listed in index kompas 100. The method of determining the sample is by using purposive sampling method, while the data processing methods used by researcher are the multiple regression analysis. The result shows that content, reporting frequency, and technology significantly influences cost of equity capital. But user support does not have a significant influence toward cost of equity capital. The result for variables control show that stock return volatility and firm size have significant influences to cost of equity capital, but industry does not have significant influences.Keywords: information, financial, internet, cost, capital